Educational Video As Evaluation Tool for Community Nurses' Cognitive Level of Dialysis Therapy - Ridha Afzal; Yuli Peristiowati (Madani: Jurnal Pengabdian Masyarakat dan Kewirausahaan, 2023)
The rise of programs to establish Continuous Ambulatory Peritoneal Dialysis (CAPD) units by the government in hospitals has not been fully anticipated by community nurses at the health center level with the same understanding regarding CAPD. The objective is through educational videos, we can evaluate the cognitive level of community nurses regarding dialysis therapy in general and CAPD in particular. This article used quantitative method with descriptive data analysis techniques. This community service-based research was compiled in June 2023. The population consisted of all health workers at the Daya Health Center, with the inclusion criteria of community nurses working at the Daya Health Center, the exclusion criteria were non-health workers or non-nurses. The instruments used were videos and questionnaires. The questionnaire consisted of two groups (demographic with 3 questions and 10 questions in nursing technique). Process the data using univariate techniques. The theory used in processing the data is Nursing Theory which includes assessment, planning, implementation, and evaluation. Data analysis was carried out descriptively. The results show there are two main problems, the first is an inadequate number of employees, especially nurses. The second is a lack of understanding of renal therapy. Twenty-six respondents took part in the questionnaire via Google Form which was distributed online. Five out of 10 questions were answered correctly by respondents (50%). These findings are the result of an evaluation that community nurses have not fully understood renal therapy. Our findings recommended that management's policy of minimal nursing staff will affect job satisfaction and the provision of short CAPD training for staff nurses.